The Role of Sleep in Insulin Sensitivity and Type 2 Diabetes Risk - Twardowska, Daria; Śliwa, Wiktoria; Tłoczek, Wiktoria; Szlachta, Wiktoria; Kret, Dominik; Anczyk , Antoni; Handzel , Karolina (Journal of Education, Health and Sport, 2026)
Sleep disturbances are increasingly recognized as important and modifiable determinants of insulin resistance and type 2 diabetes (T2D). This review provides a comprehensive synthesis of experimental, physiological, and epidemiological evidence published between 2015 and 2026 examining the relationship between sleep and insulin sensitivity. We summarize the roles of sleep duration, sleep quality, sleep architecture, and circadian alignment in the regulation of glucose metabolism, pancreatic β-cell function, and neuroendocrine pathways. Experimental studies demonstrate that short-term sleep restriction rapidly reduces whole-body insulin sensitivity and impairs β-cell responsiveness, even in the absence of weight gain. Large prospective cohorts and meta-analyses consistently link chronic short sleep, sleep fragmentation, irregular sleep timing, and circadian misalignment- including shift work- to an increased risk of incident T2D. Among individuals with established T2D, poor sleep quality, insomnia, and sleep-disordered breathing are highly prevalent and are associated with worse glycemic control and greater cardiometabolic risk. We further review evidence for sleep-focused interventions, including sleep extension, cognitive behavioral therapy for insomnia, treatment of obstructive sleep apnea, and circadian alignment strategies, which show modest but clinically meaningful improvements in insulin sensitivity and glycemic outcomes. Collectively, the evidence supports sleep optimization as an integral component of T2D prevention and management, complementing traditional lifestyle and pharmacological approaches.